COMPETITION ASPECTS IN THE AI ACT – NAVIGATING THE MURKY WATERS OF THE ABUSIVE PRACTICES IN A DECENTRALISED VIRTUAL WORLD - Iulian BĂICULESCU (Challenges of the Knowledge Society)
The whole European construction, based on the three initial European Communities (namely, the European Coal and Steel Community, the European Economic Community and the European Atomic Energy Community) were built with several goals in mind, one of them being the establishing of a fair competition, seen as an essential step in the making of an internal market. For this reason, several dispositions were enshrined in the Treaties that served as a comprehensive legal framework for prohibiting those agreements that could have distorted the competition in the community market. These provisions stand and produce important effects as we speak, but the emergence of the AI poses a new and hard to digest threat to them, as not all the dispositions regulating the competition can easily be adapted to such a new and complex reality. However, the so-called AI Act tries to tackle this issue in creative and adaptive ways that we will analyse in the following.